Purification and characterization of a novel β-1, 3-glucanase from Arca inflata and its immune-enhancing effects. (30th August 2019) - Li, Chunlei; Wen, Yao; He, Ying; Zhu, Jianhua; Yin, Xin; Yang, Jianing; Zhang, Lixin; Song, Liyan; Xia, Xuekui; Yu, Rongmin
Highlights: A novel endo -β-1, 3-glucanase was purified from blood clam Arca inflata . The glucanase was a glycoprotein and the glycosylation influenced hydrolysis activity. The glucanase exerted specific activity against laminarin and produced β-oligosaccharides. The glucanase was interestingly found to exhibit in vitro immuno-enhancing effect. Abstract: A novel β-1, 3-glucanase from Arca inflata was purified using chromatography methods. It was determined as a glycoprotein comprising 23.65% carbohydrate content with O-linked glycan and showed specific activity of 90.01 ± 1.2 U/mg against laminarin. The optimal pH and temperature for the activity of the glucanase were 6.0 and 40 °C, respectively. The affinity parameter of the glucanase using laminarin was determined as Kd = 13.09 μM. The activity of the glucanase was 27 ± 2.6% enhanced by 2-mM Mn 2+ ions and inhibited by 40–50% using 2-mM Zn 2+, Cu 2+, or Ba 2+ ions. The glucanase showed an endo -type cleavage mode and hydrolyzed laminarin into glucoses, disaccharides, trioligosaccharides, and tetraoligosaccharides. Otherwise, the glucanase exhibited immune-enhancing effects via significantly increasing the phagocytic activity of macrophages and inducing the release of nitric oxide, tumor necrosis factor α, and interleukin-6 in RAW264.7 cells. It might be used as a bifunctional additive for the food industry.